2012
DOI: 10.1111/pim.12017
|View full text |Cite
|
Sign up to set email alerts
|

Differential immune response in mice immunized with the A, R or C domain from TcSP protein of Trypanosoma cruzi or with the coding DNAs

Abstract: In a murine model of experimental Trypanosoma cruzi (H8 strain) infection, we investigated the induction of protective immunity against the domains [amino (A), repeats (R) and carboxyl (C)] of the surface protein (SP), a member of the trans-sialidase (TS) superfamily. Recombinant proteins and plasmid DNA coding for the respective proteins were used to immunize BALB/c mice, and the humoral response and cytokine levels were analysed. Immunization with the recombinant proteins induced higher levels of anti-TcSP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The analysis of the IgG subclasses produced by the immunization of canines with both recombinant plasmids revealed that the dominant antibody produced was IgG2; in a previous study in mice immunized with the pBCSP plasmid, the dominant subclass was also IgG2a [26]. These results are consistent with other studies using DNA vaccines; for example, the majority of antibodies produced were of the IgG2 subclass following immunization of dogs with a multi-component DNA vaccine containing T. cruzi trans-sialidase family genes [27].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the IgG subclasses produced by the immunization of canines with both recombinant plasmids revealed that the dominant antibody produced was IgG2; in a previous study in mice immunized with the pBCSP plasmid, the dominant subclass was also IgG2a [26]. These results are consistent with other studies using DNA vaccines; for example, the majority of antibodies produced were of the IgG2 subclass following immunization of dogs with a multi-component DNA vaccine containing T. cruzi trans-sialidase family genes [27].…”
Section: Discussionmentioning
confidence: 99%
“…This finding correlates directly with splenic tissue damage during the chronic stage of the disease. Parasite TcSP and TcSSP4 genes encode a trans-sialidase and an amastigote specific-protein, which are expressed in all forms of the parasite and in trypomastigote to amastigote transition forms, respectively, stimulating a strong humoral and cellular response during BALB/c mice infection and preventing pathological manifestations of chronic CD [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, survival was 75% in TcSSP4 gene-immunized/infected mice and 100% in those immunized with TcSP gene and then infected. These studies demonstrated protection during the chronic phase of the disease as revealed by the histological analysis showing that immunization diminishes cardiac damage caused by the H8 strain of T. cruzi (MHOM/MX/1992/H8 (T. cruzi)) [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that rSSP4 induced an antigen-specific immune response, based on the fact that ConA, MPB, or absence of stimuli do not induce this population. Moreover, the induction of Treg cells does not occur by immunization with other T. cruzi -derived recombinant antigens [17]. …”
Section: Discussionmentioning
confidence: 99%